Advancements in RP-HPLC: A Review on the Simultaneous Determination of Simvastatin and Celecoxib in Plasma - Kaur, Gurpreet; Bashir, Aqib; Gulati, Puja (Journal of Neonatal Surgery, 2025)
People use simvastatin alongside celecoxib routinely because physicians prescribe these drugs for cardiovascular and inflammatory condition management. Scientists need precise measurement of these drugs in plasma because it enables better therapeutic benefits while reducing unwanted side effects. The analysis of both simvastatin and celecoxib in plasma by Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) undergoes a complete review regarding development and validation, as well as practical implementation. The high sensitivity, along with selectivity and precision characteristics of RP-HPLC, make it an excellent tool for plasma concentration analysis of these drugs. Method development requires optimization of mobile phase composition alongside column selection and detection wavelength, together with flow rate identification. The RP-HPLC method proved suitable for both research and clinical work by validating its performance measures for accuracy, precision, LOD and LOQ, sensitivity and linearity and robustness, and specificity. RP-HPLC stands as an essential technique in the evaluation of drug pharmacokinetics and therapeutic drug monitoring, and drug interaction tests. Visiting RP-HPLC enables researchers to obtain critical data about how simvastatin and celecoxib move through the body through absorption and distribution and metabolism, and elimination (ADME) processes. The data obtained from therapeutic drug monitoring using RP-HPLC allows medical professionals to optimize drug treatment by modifying patient doses based on plasma drug levels. RP-HPLC plays an essential role in the identification of synergistic reactions among medications when patients use several drugs at once. The implementation of RP-HPLC creates several difficulties since it deals with matrix interference and sensitivity problems, and operational limitations. Advancements in column technology combined with mobile phase optimization techniques and modern detection methods via mass spectrometry will significantly improve RP-HPLC utility and accessibility in clinical practice.